2019
DOI: 10.5267/j.msl.2019.3.008
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing consumer online engagement through consumer involvement: A case of airline and hospitality services in Malaysia

Abstract: Consumer online engagement has seen a sight of emerging attention by marketing literature, but how consumer involvement, with its dimensions (importance, pleasure, sign, risk consequence, and risk probability), is linked with consumer online engagement still requires additional empirical analysis especially in the context of airline and hospitality services. The purpose of this study is to examine the relationship between consumer involvement and its dimensions and consumer online engagement. The data are coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…However, it is also known that SEO (Search Engine Optimisation) has been utilized by the industry in a proper manner based on which they have directly engaged customers towards their services and created digital marketing campaign for mentioning their digital service-oriented facilities. From the definitions of Leong et al (2019), it is also vivid that digital marketing skills develop online engagement through which the customers become able to know about the retail industries and their involvements are accelerated. Most importantly, digital marketing skills support the marketers to build an entire digital strategy while communicating with teammates through which interaction-related problems are solved with high customer involvement.…”
Section: Theme 1: Customer Engagement Using Digital Marketing Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also known that SEO (Search Engine Optimisation) has been utilized by the industry in a proper manner based on which they have directly engaged customers towards their services and created digital marketing campaign for mentioning their digital service-oriented facilities. From the definitions of Leong et al (2019), it is also vivid that digital marketing skills develop online engagement through which the customers become able to know about the retail industries and their involvements are accelerated. Most importantly, digital marketing skills support the marketers to build an entire digital strategy while communicating with teammates through which interaction-related problems are solved with high customer involvement.…”
Section: Theme 1: Customer Engagement Using Digital Marketing Skillsmentioning
confidence: 99%
“…From different sources, it has become clear that the Malaysian retail industry has different problems related to digital marketing skills for which they have faced some issues while conducting market growth processes. Mohamad et al (2019) evaluated the process of content marketing that supports the retail sector to make SEOfriendly content while strategizing and developing market features (Leong et al 2019). Depending on this process, the industry also grasps social media marketing that also becomes analytics in the marketing skills to enhance changes.…”
Section: Theme 2: Effects Of Digital Marketing To Bring Changes In Rementioning
confidence: 99%
“…a person's motivation to perform recovery, information processing and decision-making about a product or brand, also having an impact on loyalty formation. Leong et al (2019) observe it as a multidimensional construct, which encompasses aspects such as: perceived importance (compatibility with the individual's goal, personal interest and meaning); pleasure (hedonic and emotional value), sign (symbolic value, associated with individual social status, personality and identity) and risk (possibility of unwanted repercussion). Berger and Milkman (2012) and Martins et al (2019) argue that there are several reasons behind why people engage with certain content.…”
Section: Sensorial Marketingmentioning
confidence: 99%
“…Therefore, the effectiveness of advertising actions and the attitudes, motivations, interest and behavioural intentions of consumers are impacted by the variable level of involvement. Leong et al (2019) state that involvement is the antecedent of engagement, being able to influence emotional attachment and subsequent interactions with the brand or product (Cruz, Leonhardt & Pezzuti, 2017). Zhang and Yoon (2018) found that the way content is presented, and the level of consumer involvement influence the final adoption of the product, and this is mainly related to changes in consumer purchasing attitudes and intentions.…”
Section: Level Of Consumer Involvement and Purchase Intentmentioning
confidence: 99%
See 1 more Smart Citation